The Portrayal of Mortality and Its Impact on Human Behaviour in ‘They Both Die at The End’ by Adam Silvera - Muhammad Al Fatih Mahyuzar; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This study aims to explore the representation of death and its influence on human behavior in Adam Silvera's novel They Both Die at the End through Sigmund Freud's psychoanalytic approach. In the novel, the call of the